Optimization of Resource Allocation in Wireless Systems Based on Game Theory - Riahi, Sara; Hore, Ali El; Kafi, Jamal El (International Journal of Computer Sciences and Engineering, 2025)
The power allocation has for long been considered a major problem for communication between many users who share common resources. With the emergence of new paradigms such as ad hoc networks, unregulated frequency bands and cognitive radio, the study of power allocation distributed protocols becomes particularly relevant. In fact in such networks, terminals can freely choose their power allocation strategy without following the rules imposed by a central node. The terminals are considered to be independent actors and it is reasonable to consider that they are rational, that is to say, by regulating their transmission power levels, terminals wish to maximize their communication quality. In this context, it is natural to study the problem of power allocation of each terminal as part of game theory, considering the terminal as each players looking to maximize their own utility function by controlling their power emission. Game theory allows particularly to study the existence and multiplicity of balancing power allocation strategies that terminal has no interest to deviate unilaterally .In a multiple access channel, the signal from a terminal received by the other terminals as interference to their own signals. Each terminal of the transmission quality depends directly of the transmission power level of other terminals.